2010 IEEE 23rd International Conference on Micro Electro Mechanical Systems (MEMS) 2010
DOI: 10.1109/memsys.2010.5442382
|View full text |Cite
|
Sign up to set email alerts
|

Four-part differential leukocyte count using μflow cytometer

Abstract: This paper reports the four-part differential leukocyte count (DLC) of human blood using a MEMS microflow (flow) cytometer. It is achieved with a two-color laser-induced fluorescence (LIF) detection scheme. Four types of leukocytes including neutrophils, eosinophils, lymphocytes and monocytes are identified in blood samples, which are stained by fluorescein isothiocyanate (FITC) and propidium iodide (PI). The DLC results show good correlation with the count from a commercial hematology analyzer. The whole sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Holmes et al demonstrated 3-part differential count in a microfluidic device detecting lymphocytes, monocytes, and neutrophils using AC impedance counting in combination with fluorescence detection (27). Fourpart differential blood count was demonstrated by Shi et al exploiting fluorescence staining with FITC and PI (28). They succeeded in differentiating lymphocytes, monocytes, neutrophils, and eosinophils with particle count rates around 10 Hz.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…Holmes et al demonstrated 3-part differential count in a microfluidic device detecting lymphocytes, monocytes, and neutrophils using AC impedance counting in combination with fluorescence detection (27). Fourpart differential blood count was demonstrated by Shi et al exploiting fluorescence staining with FITC and PI (28). They succeeded in differentiating lymphocytes, monocytes, neutrophils, and eosinophils with particle count rates around 10 Hz.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Differentiation of blood cells is considered as one of the most promising applications of microflow cytometers (9,20,(27)(28)(29). The prospects of high-throughput analysis and separation of blood cells using micro-devices were reviewed by Toner and Irimia (6).…”
mentioning
confidence: 99%
“…Blood thermal coagulation is a complex phenomenon that encompasses several processes including deformation and rupture of erythrocytes, protein denaturation, aggregation, and blood gelation [4]. Under a heating temperature of 45˚C, the normal disc-shaped erythrocytes starts to transform into the spherocytes, and substantial fragmentation of erythrocytes occurs after the heating temperature reaches 60˚C.…”
Section: Principlementioning
confidence: 99%
“…For an example, in our previous work, a leukocyte differential count using microfluidic cytometer was successfully demonstrated [4], but without a functional valve, sample preparations could not be incorporated on the device so that an automated chip would not be possible.…”
Section: Introductionmentioning
confidence: 99%
“…T lymphocyte counts were not yet performed. Recently, four differential leukocyte counts of human blood including neutrophils, eosinophils, lymphocytes, and monocytes by a microflow cytometer were reported (Shi et al 2010). A two-color laser-induced fluorescence detection scheme was adopted.…”
Section: Introductionmentioning
confidence: 99%